KEWENANGAN BADAN MUSYAWARAH (BAMUS) NAGARI DALAM PENYELENGGARAAN PEMERINTAHAN NAGARI DI KABUPATEN AGAM (Universitas PGRI Sumatera Barat, 2013)
The function of BAMUS is to receive people’s aspiration and to be Wali Nagari’s companion in administering Nagari. BAMUS and Wali Nagari are Nagari’s officials who are able to guide and prosper Nagari’s people. Institute of Nagari’s government is stated on Peraturan Daerah Kabuten Agam number 12, 2007 which is about Nagari’s government. PERDA must regulate the organizing of Nagari, in contrary it produces some overlapping interests between BAMUS and Wali Nagari. This problem directs the researcher to conduct a research about the authority of BAMUS in administering Nagari at Kabupaten Agam. The finding of this research prove that it is rarely for BAMUS to corporate with Wali Nagari in organizing the governmence. It is happen because a conflict which is shown that both BAMUS and Wali Nagari fell that they have same opportunity in deciding systems and programs for Nagari.